Disability evaluation in patients with Guillain-Barre syndrome and SARS-CoV-2 infection - Sanchez-Boluarte, Sofía S.; Aguirre-Quispe, Wilfor; Tacunan-Cuellar, Jhon; Sanchez-Boluarte, Arantxa N.; Segura-Chavez, Darwin (Frontiers in Neurology, 2023)
Objective Several cases of Guillain-Barre syndrome (GBS) associated with SARS-CoV-2 infection have been described. This study illustrated the demographic, clinical, and neurophysiological characteristics of patients with GBS and COVID-19, as well as associated factors with disability at discharge. Materials and methods A retrospective analytical observational study was conducted. It included patients diagnosed with GBS admitted in a national reference center in Peru between 2019 and 2021. Epidemiological, clinical, neurophysiological, and cerebrospinal fluid data were analyzed. A multivariate analysis, using the generalized linear model, was performed, considering the presence of disability at discharge as the dependent variable. Results Eight-one subjects diagnosed with GBS were included. The mean age was 46.8 years (SD: 15.2), with a predominance of males (61.73%). The most frequent clinical presentation was the classic sensory-motor form in 74 cases (91.36%) with AIDP (82.35%) as the most frequent neurophysiological pattern in the group with COVID-19, while AMAN pattern predominated (59.26%) in those without COVID-19 (p = <0.000). The disability prevalence ratio at discharge between subjects with COVID-19 and those without COVID-19 was 1.89 (CI 1.06–3.34), p = 0.030, adjusted for age, sex, and neurophysiological subtype. Conclusion The neurophysiologic subtype AIDP, and a higher disability were associated with the presence of COVID-19.